2004
DOI: 10.1128/iai.72.6.3331-3335.2004
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Immunoglobulin G (IgG) and IgA to Pneumococcal Protein Antigens in a Population in Coastal Kenya

Abstract: Streptococcus pneumoniae is the primary etiological agent of community-acquired pneumonia and a major cause of meningitis and bacteremia. Three conserved pneumococcal proteins-pneumolysin, pneumococcal surface adhesin A (PsaA), and pneumococcal surface protein A (PspA)-are currently being investigated as vaccine candidates. Such protein-based vaccines, if proven effective, could provide a cheaper alternative to conjugate vaccine formulae. Few data from sub-Saharan Africa exist concerning the development of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
4
26
0
Order By: Relevance
“…Unlike the others, no further rise in anti-PsaA antibodies was seen after the age of 2 years. Studies in Finnish children have also shown early acquisition of detectable serum anti-PsaA antibodies and progressive rises in anti-Ply and -PspA antibodies over the first 24 months of life [13] and a closely similar pattern was also observed in a seroprevalence study in Kenya [32]. Both those studies and ours suggest either that in pneumococcal colonization, PsaA is more immunogenic than other antigens in the first year of life, or that anti-PsaA antibodies are induced by another non-pneumococcal cross-reacting antigenic stimulus.…”
Section: Discussionmentioning
confidence: 67%
“…Unlike the others, no further rise in anti-PsaA antibodies was seen after the age of 2 years. Studies in Finnish children have also shown early acquisition of detectable serum anti-PsaA antibodies and progressive rises in anti-Ply and -PspA antibodies over the first 24 months of life [13] and a closely similar pattern was also observed in a seroprevalence study in Kenya [32]. Both those studies and ours suggest either that in pneumococcal colonization, PsaA is more immunogenic than other antigens in the first year of life, or that anti-PsaA antibodies are induced by another non-pneumococcal cross-reacting antigenic stimulus.…”
Section: Discussionmentioning
confidence: 67%
“…Studies suggested that infants and children develop only low or undetectable concentrations of serum and salivary anti-PspA antibodies after exposure to pneumococci (24,33). Similar kinetics were observed for Kenyan children: anti-PspA IgG and IgA developed later than antibodies to other surface proteins, with concentrations slowly increasing until early childhood (16). In the sera of young Filipino infants, antibodies to PspA were detected only rarely in spite of frequent pneumococcal colonization (13).…”
mentioning
confidence: 55%
“…Concentrations of immunoglobulin G (IgG) antibodies to pneumococcal capsular polysaccharides (PPS) have been found to remain unchanged or decrease by age, depending on the serotype and the study (1,33,35). Age-specific development of antibody concentrations to pneumococcal proteins PsaA, PspA, and pneumolysin from young to old has been assessed in a Kenyan study with no decline in ageing adults (20). No previous data are available on the concentrations of IgM antibodies to PPS in the elderly, but a dramatic decline in the numbers of IgM memory B cells has been found with ageing (38).…”
mentioning
confidence: 99%